Structural and Ultrastructural Studies of Tissues Engineered Cornea - Masrudin, Siti Saleha (2010)
This study was carried out to evaluate corneal organisation and regeneration after transplantation of bilayer in vitro cornea construct (BICC) into the New Zealand White Strain rabbit’s eye. Studies were conducted to investigate the structural and ultrastructural features after corneal regeneration 90 days post-transplantation. The epithelial cells and keratocytes were isolated from the limbus of the rabbit and then cultured in vitro in 5 mL tissue culture flasks. BICC and fibrin without seeded cell construct (FWCC) were produced by mixing the epithelial cells and keratocytes with rabbit fibrin and calcium chloride (CaCl2) and maintained in culture media. The cornea was subjected to lamellar keratectomy before BICC and FWCC were implanted into the defect area. The transplanted corneas were harvested after 90 days post-transplantation for microscopic analysis and immunolabelling studies for cytokeratin 3. Slit lamp microscopic analysis revealed that engineered cornea (EC) showed good corneal regeneration with no significant difference in cornea transparency to normal cornea (NC). However, for fibrin cornea (FC), the cornea was opaque compared to NC. In addition, the defect cornea (DC), which was cornea without implantation after lamellar keratectomy, showed a transparent cornea similar to NC. Morphometric analysis of the corneal thickness was done by using Least Significant Difference (LSD) test and Analysis of Co-Variance, showed that EC was capable of regenerative similar thickness functional cornea as NC when compared to FC and DC (p<0.05). Scanning electron microscope (SEM) analysis demonstrated that epithelial surface of EC showed significantly similar features to NC compared to FC and DC (p<0.05). Transmission electron microscope (TEM) analysis showed that the basal lamina development of EC was similar to NC with the establishment of cell junction compared to FC and DC. Furthermore, the EC showed a compact stromal organization with homogenous collagen fibrils diameter similar to NC (p<0.05). However, FC and DC showed a loose stromal organization with heterogenous fibrils diameter, with FC fibrils diameter were bigger than that of NC; while for DC, the fibrils diameter was smaller than NC (p<0.05). Confocal microscopy analysis confirmed that the regenerated epithelial cells in all groups were corneal epithelial cells by using corneal differentiation marker, cytokeratin 3 (CK3). As a conclusion, the EC demonstrated excellent regenerative ability of cornea and better wound healing.